Moving toward co-production: five ways to get a grip on collaborative implementation of Movement Behaviour curricula in undergraduate medical education - Morgan, Tamara L; Nowlan Suart, Theresa; Fortier, Michelle S; Tomasone, Jennifer R (Canadian Medical Education Journal, 2022)
Several “calls to action” have imposed upon medical schools to include physical activity content in their overextended curricula. These efforts have often neither considered medical education stakeholders’ views nor the full complexity of medical education, such as competency-based learning and educational inflation. With this external pressure for change, few medical schools have implemented physical activity curricula. Moreover, Canada’s new 24-Hour Movement Guidelines focus on the continuum of movement behaviours (physical activity, sedentary behaviour, and sleep). Thus, a more integrated process to overcome the “black ice” of targeting all movement behaviours, medical education stakeholder engagement, and the overextended curriculum is needed. We argue for co-production in curriculum change and offer five strategies to integrate movement behaviour curricula that acknowledge the complexity of the medical education context, helping to overcome our “black ice.” Our objectives were to investigate 24-Hour Movement Guideline content in the medical curriculum and develop an integrated process for competency-based curriculum renewal. Stakeholders were equal collaborators in a two-phased environmental scan of 24-Hour Movement Guideline content in the Queen’s University School of Medicine. Findings and a working curriculum map highlight how new, competency-based content may be embedded in an effort to guide more relevant and feasible curriculum changes